I am one of you! Team prototypicality as a facilitator for female leaders - Hernandez Bark, Alina S.; Monzani, Lucas; van Dick, Rolf (Frontiers in Psychology, 2022)
In the present study, we complement role congruity theory with insights from the Social Identity Model of Leadership. We propose that especially female leaders benefit from team prototypicality, i.e. being representative of the group they are leading. We assume that team prototypicality shifts the comparative frame away from higher-order categories like gender and leader roles to more concrete team-related properties and thereby reduces disadvantages for female leader that stem from the incongruity between the leader role and the female gender role stereotypes. Further, this effect should affect both (female) leaders themselves and their perception by their followers. Building on previous research, we predict, first, lower authentic leadership behavior for female than male leaders. Second, that team prototypicality positively relates to authentic leadership and trust in leader. Third, that team prototypicality has stronger relations to authentic leadership and trust in leader for female compared to male leaders. We tested assumptions in a randomized online experiment (Study 1, N = 315) and a cross-sectional survey study (Study 2, N = 300). We did not find consistent support for the assumed gender differences in authentic leadership. But, our results (both in manifest and in latent analyses) show that team prototypicality – both self-perceived (Study 1) and as perceived by employees (Study 2) – is related to more authentic leadership and more trust in leader (Study 2) and that these relations are stronger for female than for male leaders. Furthermore, we tested in Study 2 an extended model including follower’s job satisfaction as final follower outcome affected via team prototypicality, leader gender, authentic leadership and trust in leader. Thereby, we found that team prototypicality has direct and indirect effects on job satisfaction as carried through authentic leadership and trust in leader, respectively. Together, the results of both studies support our assumptions and show that female leaders can reduce role incongruity barriers through high team prototypicality. Implications for future research and practical implications of these results for gender equality are discussed.